Live imaging of synaptic vesicle release and retrieval in dopaminergic neurons - Mani, Meera; Ryan, Timothy A. (Frontiers in Neural Circuits, 2009)
Dopaminergic (DA) neurons represent less than 0.01% of neurons in the human brain, but are essential for normal neurological and psychiatric function. The majority of these neurons reside in the ventral midbrain, but they exert their profound influences on brain function through projections to both the cortex and the basal ganglia. These projections secrete dopamine from small clear synaptic vesicles (SVs) in axonal varicosities. DA signaling has unique spatial and temporal characteristics as compared to the fast, focal synaptic transmission of excitatory and inhibitory neurons. However, as with fast acting neurotransmitters, DA SVs must be locally recycled for use following exocytosis. Little is known about these DA SV recycling properties and how they might impact efficacy of DA neurotransmission. Here we used the pH-sensitive fluorescent probe synaptopHluorin (spH) to investigate SV recycling in DA neurons and compared their properties to prototypical fast neurotransmitter synapses of the hippocampus. These measurements showed that DA SVs, like hippocampal SVs, have a resting pH of ~5.6. However, compared to hippocampal neurons, DA neurons show limited depletion of the recycling pool of vesicles as the stimulus frequency is increased from 5 to 30Hz. Additional measurements show that exocytosis rates at this frequency are comparable between hippocampal and DA neurons. Thus, limited vesicle depletion likely arises from a stimulus frequency-dependent acceleration of DA SV endocytosis or re-acidification. Our observations imply differential regulation of endo-exocytic balance in dopaminergic neurons. Finally, our assay can also be used to investigate the effects of genetic and chemical modulation of the synaptic vesicle cycle.